Cavitation in lubricating films - Letchford, N (2016)
Wear and friction are signicant problems in machinery. A particularly harsh environment is the space between the piston ring and cylinder wall of a combustion engine. Lubricant lms are commonly used to mitigate these eects, separating metal to metal contact. The experiments of Zhu and Granick (Langmuir, 18, 2002) attempt to understand how surfactants change the behaviour of lubricating lms. They claim surfactants that have adsorbed onto a solid surface cause the uid to slip past the surface. We hypothesize that their observations could instead be caused by the liquid cavitating. We develop a mushy region model, based on the work of Ockendon, Howison, and Lacey (Q J Mech Appl Math, 56, 2003), to represent the cavitated region which we assume is composed of liquid, vapour, and gas. We show that the normal force predicted by the model gives a good t to experimental observations. We also model experiments of Professor J. Nouri, who investigated the formation of gaseous cavities in a slider bearing, again using a mushy region model. We present a detailed asymptotic analysis of the model and show how the solution changes from being quasi-steady to dynamic as the velocity of the bottom surface changes sign. We show that numerical solutions of the model are in good qualitative agreement with experimental measurements, yet several persistent discrepancies remain. We suggest possible causes of these discrepancies, and estimate the eects that various physical phenomena might have on the experiments. By modifying the mushy region model to study the impact of various additional processes on the lm, we attempt to explain specic dierences between the model and the experimental results. We also extend the model to include other eects so it is more representative of the operating conditions experienced by lubricants in engines.